TOURIS MARKETING THROUGH VIRTUAL AND AUGMENTED REALITY (VR/AR) TECHNOLOGIES - Anvarova , Muhsinakhon (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This scientific article explores the role of Virtual Reality (VR) and Augmented Reality (AR) technologies in modern tourism marketing. The study analyzes how immersive technologies influence tourists’ perceptions, engagement levels, and travel decision-making processes. Using a mixed-method approach that combines surveys, expert interviews, and case studies, the research identifies that VR and AR significantly enhance destination image, brand awareness, and customer experience. The findings also highlight the contribution of VR/AR to sustainable tourism development by reducing the need for physical travel during the pre-visit stage and promoting accessibility for all user groups. Ultimately, the study concludes that the effective integration of VR and AR technologies into marketing strategies can increase destination competitiveness, foster innovation, and strengthen emotional connections between destinations and tourists.